NCOG-40. UTILITY OF THE SEIZURE CONTROL COMPOSITE INDEX (RANO-SCCI) IN EVALUATING SEIZURES IN CNS TUMOR PATIENTS. (14th November 2022) - Miller, Hope; Christ, Alexa; Grajkowska, Ewa; Acquaye, Alvina; Adegbesan, Kendra; Boris, Lisa; Burton, Eric; Chambers, Claudia; Choi, Anna; Evans, Karen; King, Amanda; Komlodi-Pasztor, Edina; et al.
Abstract: BACKGROUND: Seizures are a common symptom in patients with CNS tumors. The RANO-Seizure Control Composite Index (RANO-SCCI) was developed to monitor seizures over time by patients and clinicians. We describe the use of the RANO-SCCI as part of the NCI NOB-Natural History Study. METHODS: Patients completed a RANO-SCCI prior to their clinic appointment with results shared with clinicians who then completed a RANO-SCCI as part of the same appointment. Seizure reports were tallied by respondent type and further by tumor type and grade. Concordance between patient and clinician report was also investigated. RESULTS: One hundred fifty-seven patients underwent 250 clinical evaluations. Participants were primarily white (82%) males (57%) with median age 47 years (range: 19 – 78). Most had high grade (60%) primary brain (86%) tumors, were in surveillance (76%), with no prior recurrence (57%) and KPS ≥ 90 (76%). Half of patients and 62% of clinicians reported the patient ever having a seizure. The 12% discordance were all where the patient did not report a seizure, but clinicians did. There was good agreement on seizure reporting since last visit (74% patients, 78% clinicians), and anti-seizure medication use (51% patients, 57% clinicians). Seizures were reported more frequently in patients with high-grade tumors (WHO Grade 3 or 4) (60% patients, 76% clinicians) versus low-grade (WHO Grade 1 or 2) (51% patients, 59% clinicians), and among patients with oligodendrogliomas (71% patients, 85% clinicians) versus non-oligodendroglioma tumors (54% patients, 68% clinicians). CONCLUSIONS: The RANO-SCCI was used for self-report and clinician report of seizure activity. A higher frequency was reported among oligodendroglioma and high-grade tumors. Disparities between patient and clinician responses may reveal a limitation in the patient's ability to recognize and assess their seizure symptoms. Further work will investigate reporting congruence and associations with clinical and demographic characteristics.